The Role of Motivation in Students’ Learning Process - Bunga Maula; Jasiah Jasiah (The Future of Education Journal, 2026)
Motivation is one of the crucial factors influencing the success of students’ learning processes. This article aims to examine the role of motivation in improving the quality of learning and students’ academic achievement. The study employs a literature review approach by analyzing various theories and research findings related to learning motivation. The analysis reveals that both intrinsic and extrinsic motivation significantly influence students’ interest, active participation, and persistence in learning activities. Students with high levels of motivation tend to demonstrate greater concentration, enthusiasm, and academic achievement compared to those with lower levels of motivation. Furthermore, teachers, learning environments, and parental support play important roles in fostering and strengthening students’ motivation to learn. These factors contribute to creating meaningful learning experiences that encourage students to achieve their full academic potential. Therefore, innovative teaching strategies and appropriate instructional approaches are necessary to ensure the continuous development of students’ motivation. Strengthening learning motivation is expected to enhance the effectiveness of the learning process and improve students’ academic outcomes in various educational settings.